2016 ASAHP Annual Conference: Abstracts of the Presentations…Assessing Challenges in Clinical Education: A Case Study of a Cardiopulmonary Science Program at a Historically Black College & University. - Simmons, Mary V.; Lopez, Ivette A.; Woods, Kandy T.; Simmons, Jazmyne V. (Journal of Allied Health)
Issue: Florida A&.M University is a historically black college &. university (HBCU). Since its inception in October 1887 it has provided higher education opportunities to African American and minority students. As the only Bachelor of Science Cardiopulmonary program at an HBCU in the state of Florida, we have produced generations of practicing registered respiratory therapists. Contributions to this success seem to be the clinical rotations in our local health facilities. Therefore, this study was designed to formally gather data on students' clinical experiences and to identify potential challenges in their clinical education. Method: Semi-structured phone interviews were conducted with past students. No current students were interviewed, as we did not want participants to feel pressured into answering favorably. Observations/Outcomes: Preliminary data analysis yielded inconsistent clinical experiences between facilities. Students' reported receiving less hands-on training at some facilities versus other. Participants also reported experiencing a more welcoming environment at some facilities versus other facilities; thus improving their learning experience. Conclusion: Based upon our preliminary assessment, clinical rotations have contributed to job opportunities and increased self-efficacy. However, there are gaps within the clinical experience that need improvement. Additional data are being gathered through clinical site preceptors to create a holistic picture of determinates of success.